Efecto de la aplicación de tres bioestimulantes en el cultivo de Espinaca (spinacea oleracea l), en la Zona de Izamba, provincia de Tungurahua - Díaz Valencia, Maritza Fernanda (2015)
The present investigation was carried in Izamba parish, Ambatocanton, Tungurahua county, whose coordinated geographical are: 01 43'00” of South latitude and 78 30 ' 00”West longitude, to altitude of 2.427 m.s.n.m., with the purpose: establish the bioestimulant (Wuxal Doble, Bayfolan Aktivator and Wuxal Ascofol) and the effective dose (1 l/ha, 2 l/ha and 3 l/ha), to increase growth and development of spinach plants (Spinacea oleracea L) Viroflayinvernvariety, as well as, evaluate the productive yield of crop and to analyze the treatments economically. The treatments were nine that received bioestimulants foliaresapplication, more an absolute witness. The experimental design of blocks was used totally at random with 3 x 3 + 1 factorial arrangement, with four replications. The variancia analysis was made (ANOVA); Tukey 5%significance tests, to differ among treatments, bioestimulantes, dose and interaction that were significant. Tests orthogonals comparisons for bioestimulantes factor and orthogonals polynomials with regression calculation and correlation for dose factor, for the variables foliage longitude, number of leaves for plant, leaf longitude, days to the crop, yield for parcel and yield for hectare. The economic analysis they were considered the total costs, total revenues, index of profitability, direct costs and the gross margin of contribution and the appraisement of the yield in American dollars of the price of the kilogram of spinach, for finally to obtain the biggest net entrance for hectare.............